Intensity of integrated cancer palliative care plans and end‐of‐life acute medical hospitalisation among cancer patient in Northern Italy. (15th August 2017) - Pellizzari, Michele; Rolfini, Maria; Ferroni, Eliana; Savioli, Valentina; Gennaro, Nicola; Schievano, Elena; Avossa, Francesco; Pinato, Elisabetta; Ghiotto, Maria Cristina; Figoli, Franco; Mantoan, Domenico; Brambilla, Antonio; et al.
Abstract : A high hospital utilisation at the end of life (EOL) is an indicator of suboptimal quality of health care. We evaluated the impact of the intensity of different Integrated Cancer Palliative Care (ICPC) plans on EOL acute medical hospitalisation among cancer decedents. Decedents of cancer aged 18–84 years, who were residents in two Italian regions, were investigated through integrated administrative data. Outcomes considered were prolonged hospital stay for medical reasons, 2+ hospitalisations during the last month of life and hospital death. The ICPC plans instituted 90 to 31 days before death represented the main exposure of interest. Other variables considered were gender, age class at death, marital status, recent hospitalisation and primary cancer site. Among 6, 698 patients included in ICPC plans, 44.3% presented at least one critical outcome indicator; among these, 76.5% died in hospital, 60.3% had a prolonged (12+ days) medical hospitalisation, 19.1% had 2+ hospitalisations at the EOL. These outcomes showed a strong dose–response effect with the intensity of the ICPC plans, which is already evident at levels of moderate intensity. A well‐ICPC approach can be very effective—beginning at low levels of intensity of care—in reducing the percentage of patients spending many days or dying in hospital.